Primary Care Physician Perspectives on Low Risk Prostate Cancer Management: Results of a National Survey. Issue 4 (22nd July 2021) - Radhakrishnan, Archana; Wallner, Lauren P.; Skolarus, Ted A.; Shahinian, Vahakn B.; Abrahamse, Paul H.; Fetters, Michael D.; Hawley, Sarah T.
Abstract: Introduction: Primary care providers can collaborate with urologists to ensure men with low risk prostate cancer on active surveillance receive followup testing and adhere to the management strategy, yet primary care provider attitudes about active surveillance and their roles remain unknown. Methods: We surveyed 1, 000 primary care providers (347/741 eligible primary care providers responded). We assessed primary care provider support for and beliefs about active surveillance, and attitudes about and preferences for their role in various aspects of low risk prostate cancer management. We then examined associations between 1) primary care provider support for and primary care provider beliefs about active surveillance; and 2) primary care provider attitudes and preferences for their role. Results: Nearly 50% of primary care providers strongly supported active surveillance for all low risk men, and 81% strongly agreed that active surveillance allows men to avoid side effects, while 57% strongly agreed it caused worry. Primary care providers who strongly supported active surveillance were less likely to strongly agree that active surveillance contributes to worry (50.3% vs 63.7% respectively, p=0.01). Half of the primary care providers strongly agreed that primary care providers can provide cancer-related care (50.5%), and the majority preferred a shared care model to ordering prostate specific antigen tests (60.1%). Primary care providers who strongly agreed that primary care providers can provide cancer-related care were more likely to prefer a primary care provider-led (79.3% vs 20.7%) or shared care (53.9% vs 46.1%) model vs urologist-led for ordering prostate specific antigen tests (p <0.01). Conclusions: While many primary care providers supported active surveillance for low risk prostate cancer, primary care providers still had concerns with it as the primary management strategy. Understanding primary care providers perspectives on low risk prostate cancer management can inform strategies to improve high quality active surveillance care.